Miyazakia, a new aphid genus from Japan (Hemiptera: Aphididae: Macrosiphini) - Stekolshchikov, Andrey V. (Zootaxa, 2014)
Miyazakia gen. nov. with type species Miyazakia ranunculi (Miyazaki, 1971) comb. nov. is described. The species is illustrated and biometric data are provided for all morphs, except the fundatrix. This aphid genus is closely related to Sappaphis Matsumura, 1919. M. ranunculi is a heteroecious species; its primary host is probably Photinia villosa (Thunb.) DC and its secondary host is Ranunculus.